Subject Student Teachers' Perceptions of Key Environmental Problems and Their Own Role as Environmental Problem Solvers - Eija Yli-Panula; Eila Jeronen; Sofia Vesterkvist; Laura Mulari (MDPI AG, 2023)
Teachers play a crucial role in supporting the development of students' environmental knowledge and skills for responding to environmental change, but previous research has not sufficiently explored teachers' perceptions of this matter. The article reports on a survey aimed at studying subject student teachers' (SSTs, n = 113) perceptions of environmental problems, their interest in sustainable development (SD) and their own role as environmental problem solvers. The material was gathered using a questionnaire and analysis by quantitative methods. Urban environment and infrastructure problems were the most frequently mentioned. Problems of ecosystems and indifference and a lack of information were also mentioned often, while the least noted were problems of human wellbeing. The majority of SSTs were interested in SD, but interest in SD was dependent on the discipline studied and gender. Two-thirds of women and one-third of men were very interested, and more than half of biology and geography SSTs were very interested. Over half of SSTs reported that environmental problems had to be solved by someone else; only about one-seventh perceived themselves to be solvers. The SSTs felt that they could influence the solutions to environmental problems more often on a local than on a regional or global level.